The Effect of Training, Competence and Loyalty on Employee Performance with Employee Engagement as a Moderation Variable in PT Pelindo Multi Terminal - Farid Chairmawan; M. Chaerul Rizky; Kholilul Kholik (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of training, competence, and loyalty on employee performance with employee engagement as a moderation variable at PT Pelindo Multi Terminal Branch Belawan. This study uses a quantitative approach with a causal associative research method to test the cause-effect relationship between variables. The research population is all employees of PT Pelindo Multi Terminal Branch Belawan which totals 40 people, with the sample determination technique used is the census technique (saturated sampling). Data was collected through a questionnaire with a Likert scale that has been tested for validity and reliability. The data analysis technique used Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software version 4.0 to test the measurement model (outer model) and structural model (inner model), as well as to analyze the effect of employee engagement moderation on the relationship between independent and dependent variables. The results show that training and competencies have a positive and significant effect on employee performance, with competence as the most dominant factor. However, loyalty and employee engagement also do not have a significant effect on employee performance. For the moderation relationship, the employee engagement variable was not shown to moderate the relationship between employee competence and performance, nor did it moderate the relationship between employee loyalty and performance, nor did it moderate the relationship between training and employee performance. The research model has an R² value of 0.739 which shows that the variables of training, competence, loyalty, and employee engagement are able to explain 73.9% of the variation in employee performance, with a Q² value of 0.739 which indicates excellent predictive relevance.